Modification of the hydro-thermal mineral-forming fluid composition in the Early Precambrian of the Earth - Demikhov, Yu.N.; Fomin, Yu.A.; Verkhovtsev, V.G.; Pokalyuk, V.V.; Borisova, N.N. (Reports of the National Academy of Sciences of Ukraine, 2020)
Based on the experimental isotope-geochemical study of the fluid of gas-liquid inclusions in the minerals of the Early Precambrian deposits of gold and uranium of the Ingul megablock and Srednepridneprovsk granitegreenstone belts of the Ukrainian shield, a decrease in the content of carbon dioxide and light carbon dioxide is found in hydrothermal mineral-forming fluids at the Archaean-Proterozoic boundary. The molar part of CO2 in mineral-forming fluids to a certain extent correlates with atmospheric pressure. The evolution of the Earth’s outer shells at the Archean-Paleoproterozoic boundary, which was manifested globally by a change in the atmosphere from oxygen-free to oxygen and a decrease in carbon dioxide content, is compared with a change in the endogenous processes of the formation of ore-and mineral-forming hydrothermal fluids. An increase in the oxygen content in the Precambrian atmosphere occurred later than a decrease in the carbon dioxide content in the mineral-forming fluid. An increase in the content of the light carbon isotope in the Paleoproterozoic mine ralforming fluid was probably due to the oxidation of organic matter due to the appearance of photosynthesis.